Light sintering process suitable for high-throughput manufacturing of perovskite solar cell device

By using pulsed photo-sintering technology and ABX3-type perovskite structure, combined with sulfone or sulfoxide additives, and optimizing photo-sintering parameters, the problems of low photoelectric conversion efficiency and industrial production of perovskite solar cell devices were solved, achieving efficient perovskite thin film preparation and improved device performance.

CN119486558APending Publication Date: 2025-02-18NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411553829.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the existing technology, perovskite solar cell devices have low photoelectric conversion efficiency, and traditional thermal annealing processes cannot meet the needs of high-throughput industrial production.

Method used

A pulsed photo-sintering process was adopted to regulate the crystallization and solidification process of the perovskite photoactive layer through synergistic photochemical effects. By combining the ABX3 type perovskite structure and sulfone or sulfoxide additives, the photo-sintering parameters were optimized to prepare high-quality perovskite thin films.

Benefits of technology

It improves the photoelectric conversion efficiency of perovskite solar cell devices, broadens the photo-sintering window, reduces the generation of PbO states during heat treatment, is suitable for flexible substrates and environmental environments, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486558A_ABST
    Figure CN119486558A_ABST
Patent Text Reader

Abstract

The invention discloses a light sintering preparation method of a perovskite light active layer, and the method employs a strong pulse light sintering preparation method, greatly widens a light sintering window, is not liable to generate an overburning condition, can effectively reduce a PbI2 or Pb0 state generated in a heat treatment process, optimizes a perovskite surface energy level state, reduces the residual stress of a film, improves the effectiveness of light sintering, and improves the performance of light sintering. The photoelectric property of the perovskite thin film is improved, and the steady-state fluorescence intensity of the thin film is improved. Besides, the strong pulsed light sintering method is short in sintering time, shows good compatibility in a flexible substrate and an environment atmosphere, can be used for preparing a perovskite solar cell device in a high-flux manner, and is effectively matched with industrial production. The invention further discloses a solar cell of the perovskite photoactive layer prepared based on the intense pulsed light sintering method, and the device efficiency is further improved by more than 23%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a photo-sintering process suitable for high-throughput manufacturing of perovskite solar cell devices. Background Art

[0002] At present, the photoelectric conversion efficiency of perovskite solar cell devices (PSCs) has reached 26.7%, which is comparable to that of single-crystal silicon solar cells. In the process of solar cell industrialization, in addition to paying attention to the photostability and thermal stability of perovskite solar cell devices, the preparation process of perovskite solar cell devices is also a research hotspot. The annealing step plays an important role in the manufacturing process of perovskite solar cell devices. It affects the nucleation and growth of the perovskite photoactive layer to a certain extent, and then affects the performance of the device. At present, the annealing methods used in the laboratory are mainly hot stage annealing or convection oven, collectively referred to as thermal annealing. However, these annealing processes require a processing time of more than 10 minutes, which cannot match high-throughput industrial production. Therefore, the development of new heat treatment processes is an urgent need.

[0003] Intense Pulsed Light (IPL) is a heat treatment technology based on photothermal conversion. It has many names in academia and applications, such as Flash Annealing, Photonic Annealing, Photonic Curing, and Flash Infrared Annealing. IPL uses synergistic photochemical effects. The pulse width of the photothermal phenomenon is in the order of microseconds to milliseconds. It can heat the material to a certain temperature very quickly without damaging the room temperature or low temperature substrate. Therefore, IPL has the characteristics of fast sintering, good economic benefits, small footprint, and easy compatibility with "roll-to-roll" process production. It gradually replaces traditional annealing treatment and is widely used in thin film transistor doping in semiconductor processes, conductive ink curing in printed electronic products, and thin film annealing in display technology.

[0004] At present, photo-sintering is also used in perovskite devices, such as photo-sintering of the transmission layer and the active layer. For example, the publication number US2017250030A1 discloses a method of preparing a CH3NH3PbI3 perovskite solar cell device thin film by fast sintering with an intense pulse light source. The film is prepared based on a single pulse in the intense pulse light sintering process, making the photoelectric conversion efficiency exceed 12%, the preparation time is shortened to 2ms, and the crystal structure remains unchanged during the preparation process.

[0005] In addition, reference 1 (Recrystallized Perovskite Thin Film via Intense Pulse Light Sintering for Vertical Gradient Band Gap Perovskite Solar Cells [J], ACS Appl. Energy Mater. 2021, 4, 14240-14248.) discloses a method for preparing a perovskite film with a vertical gradient band gap based on intense pulsed light sintering, by directly inkjet printing MAPbBr3 quantum dots on a spirally coated MAPbI3 film to construct a stacked perovskite layer (MAPbBr3QD / MAPbI3). The stacked perovskite film was sintered by single pulse light sintering; after sintering, the grain size of the stacked layer increased significantly, and at the same time, a mixed halide perovskite (MAPbBr) with a gradient was formed between the stacked layers. 3-x I x ) film, the photoelectric conversion efficiency reached 17.06%, and the moisture stability was 80% after being treated for 500h under a relative humidity (RH) of 70%.

[0006] Currently, a single-pulse light sintering process is used to prepare perovskite solar cell devices, which greatly shortens the preparation time. However, most of the processes are targeted at MAPbI3 perovskite components and have not been applied to more stable formamidine / cesium perovskite components. In addition, the photoelectric conversion efficiency of solar cells obtained using single-pulse light sintering technology is low (less than 20%), which in turn limits the high-throughput preparation of thin films of perovskite solar cell devices. This is also an urgent problem to be solved in the transfer of perovskite solar cell devices from devices to industrial scale. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a method for preparing a perovskite photoactive layer by photo-sintering, introduces pulse group photo-sintering, realizes the crystallization and solidification process of perovskite through synergistic photochemical action, and is used for high-throughput preparation of perovskite photoactive layer, thereby further improving the photoelectric conversion efficiency of perovskite solar cell devices and realizing the transfer of perovskite solar cell devices from devices to industrial scale.

[0008] A method for preparing a perovskite photoactive layer by photo-sintering, comprising the following steps:

[0009] (1) preparing a precursor solution of a perovskite photoactive layer;

[0010] (2) spreading the precursor solution of the perovskite photoactive layer prepared in step (1) on the hole transport layer substrate, and extracting it to form a perovskite intermediate state;

[0011] (3) Using an intense pulsed light sintering method, the perovskite intermediate state obtained in step (2) is subjected to pulsed light sintering to obtain a perovskite photoactive layer.

[0012] The present invention uses pulse group photosintering to perform photosintering on the intermediate state of perovskite, which can realize short-interval pulses to accurately control the change of the intermediate state temperature field, affect the crystallization and solidification process of the perovskite active layer, and realize high-quality perovskite film growth.

[0013] Preferably, the precursor solution of the perovskite photoactive layer contains crystals of ABX3 perovskite structure; wherein A is one or more of methylammonium cation, formamidinium cation, cesium ion, and rubidium ion, B is one or more of lead ion and tin ion, and X is one or more of chloride ion, bromide ion, iodide ion, and thiocyanate ion.

[0014] ABX3-type perovskite structured crystals have a high defect tolerance. The use of a precursor solution containing ABX3-type perovskite structured crystals to prepare a perovskite photoactive layer helps to improve the stability of perovskite solar cell devices. And by adjusting the components of ABX3, the band gap of the perovskite material can be changed, thereby improving the flexibility of the application of perovskite solar cell devices.

[0015] Preferably, a sulfone or sulfoxide additive is added to the precursor solution of the perovskite photoactive layer.

[0016] Sulfone or sulfoxide additives are added to the precursor solution of the perovskite photoactive layer to regulate the intermediate state of the perovskite, produce a strong effect with PbI2, and combine with photo-sintering to inhibit the Pb 0 The generation of states can improve the photoelectric conversion efficiency of perovskite solar cell devices.

[0017] Preferably, the sulfone or sulfoxide additive added to the precursor solution is dimethyl sulfone, dodecyl methyl sulfoxide or dimethyl sulfoxide.

[0018] Preferably, the molar percentage of the sulfone or sulfoxide additive in the precursor solution of the perovskite photoactive layer is 0.1-40%.

[0019] Further preferably, the molar percentage of the dodecyl methyl sulfoxide or dimethyl sulfone in the precursor solution of the perovskite photoactive layer is 0.1-4%; the molar percentage of the dimethyl sulfoxide in the precursor solution of the perovskite photoactive layer is 10-40%.

[0020] Preferably, the precursor solution is spread by spin coating, blade coating or slit coating.

[0021] Choosing a suitable method of spreading the precursor solution can greatly shorten the coating speed, improve the utilization rate of the precursor solution, and obtain a film with high precision and uniform wet thickness.

[0022] The preparation of the hole transport layer substrate comprises: firstly ultrasonically cleaning the substrate, drying it with high-pressure inert gas, and then irradiating it with ultraviolet light to obtain a cleaned substrate; then spin coating the hole transport layer material on the cleaned substrate and annealing it to prepare the hole transport layer substrate.

[0023] Preferably, the extraction is performed by air knife, anti-solvent or vacuum drying.

[0024] Extraction by air knife, anti-solvent or vacuum drying can accelerate the crystallization of perovskite, thereby obtaining a large area of ​​high-quality perovskite intermediate state and improving the energy conversion efficiency of solar cell modules.

[0025] Preferably, the pulse group photo-sintering is to place the perovskite intermediate state into a photo-sintering cavity, and adjust the pulse group photo-sintering parameters to implement the pulse group photo-sintering process.

[0026] Pulse group photo-sintering affects the thickness and uniformity of the perovskite photoactive layer by adjusting parameters. Selecting appropriate parameters can avoid structural changes or decomposition of the perovskite material, regulate the crystallization and solidification process of the perovskite material, obtain a photoactive layer with good crystallinity and density, and improve the efficiency of the device.

[0027] The pulse group light sintering is selected from the pulse light source irradiated by a xenon lamp.

[0028] Preferably, the pulse group optical sintering parameters are: sintering voltage 500-2000V, pulse width 1-3000μs, each pulse group contains 1-15 small pulses, the interval between each small pulse is 5-3000μs, and the pulse interval is 5-10000ms.

[0029] Further preferably, the pulse group photosintering voltage is 1000 V, the pulse width is 500 μs, each pulse group contains 5 small pulses, the interval between each small pulse is 1000 μs, and the pulse interval is 1000 ms.

[0030] Preferably, the pulse group light sintering process is as follows: the sintering height between the pulse light source and the photoactive layer is ≤1000 mm, and the number of sintering times is ≤50 times.

[0031] Further preferably, the sintering height between the pulse light source and the photoactive layer is 40 mm, and the sintering times are 7 to 11 times.

[0032] The present invention also provides a perovskite photoactive layer prepared by the preparation method.

[0033] Preferably, the perovskite photoactive layer is FA 1-x-y MA x Cs y Pb(I 1-z Br z )3, where x=0~1, y=0~1, z=0~1.

[0034] Further preferably, the perovskite photoactive layer is FA 0.85 MA 0.1 Cs 0.05 PbI3、FA 0.9 Cs 0.1 PbI3 or FA 0.95 Cs 0.05 (I 0.95 Br 0.05 )3.

[0035] In order to illustrate the influence of the photo-sintering preparation method on the photoelectric conversion efficiency of a perovskite solar cell device or a micro-module, the present invention also provides a solar cell device or a micro-module based on an ABX3 perovskite photoactive layer.

[0036] The solar cell device or micromodule provided by the present invention comprises a substrate, a surface electrode, a hole transport layer, an ABX3 perovskite photoactive layer, an electron transport layer, an interface regulation layer and a back electrode, wherein the substrate is a flexible substrate or glass;

[0037] The surface electrode is a transparent conductive film;

[0038] The hole transport layer is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], copper thiocyanate, aluminum oxide, nickel oxide and / or single molecule self-assembled phosphonic acid.

[0039] The electron transport layer is fullerene, phenyl-C61-butyric acid methyl ester, tin dioxide, cerium oxide or titanium dioxide;

[0040] The interface regulating layer is bathocuproin or tin dioxide;

[0041] The back electrode is a metal electrode and / or a transparent conductive film.

[0042] Selecting substrates and electrodes with high light transmittance and good conductivity can improve the energy conversion efficiency of the device and reduce the resistivity of solar cells; the electron and hole transport layers have a wide band gap, a small refractive index and a high electron mobility, which can promote the effective separation of electrons and holes, reduce charge recombination and eliminate hysteresis; the interface regulation layer can enhance carrier transport, prevent the dissociation of the surface structure of the perovskite crystal, and thus improve the stability of the device; the back electrode has good conductivity and stability, which can solve the problem of back electrode contact in traditional devices and improve the efficiency and stability of the device.

[0043] Preferably, the flexible substrate is polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI) or ultra-thin flexible glass (UTG).

[0044] Choosing a flexible substrate can broaden the application scenarios of perovskite solar cell devices and enable large-scale industrial production.

[0045] The transparent conductive film is indium tin oxide, indium tin fluoride or aluminum-doped zinc oxide.

[0046] Indium tin oxide (FTO), indium tin fluoride (FTO) or aluminum-doped zinc oxide (AZO) has a large bandgap, provides high visible light transmittance and near-infrared transmittance, and has very low resistivity, which can effectively improve conductivity.

[0047] Preferably, the single-molecule self-assembling phosphonic acid is [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(7H-dibenzo[c,g]carbazole-7-yl)butyl]phosphonic acid (4PADCB), [4-(3,11-dimethoxy-7H-dibenzo[c,g]carbazole-7-yl)butyl]phosphonic acid (MeO-4 Phosphonic acid (PADBC), [2,7-dimethoxy-9H-carbazol-9-yl)methyl]phosphonic acid (DC-PA), [2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl]phosphonic acid (MPA-CPA), [4-(3,6-methyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz), [2-(3,6-dimethoxy-9H-carbazol-9-yl)butyl]phosphonic acid (MeO-4PACz).

[0048] Single-molecule self-assembled phosphonic acid has high hole selectivity, high hole transfer rate and low interface trap state density. It has a stable lattice structure that can suppress light-induced halide segregation to enhance the stability of the device. It also has molecular designability and excellent mechanical flexibility to match the industrial production of perovskite solar cell devices.

[0049] Preferably, the solar cell device or micromodule comprises: FA 0.85 MA 0.1 Cs 0.05 PbI3 perovskite photoactive layer; in the preparation of FA 0.85 MA 0.1 Cs 0.05 When the PbI3 perovskite photoactive layer is prepared, a sulfone or sulfoxide additive is added to the precursor solution of the perovskite photoactive layer, and the sulfone or sulfoxide additive is dodecyl methyl sulfoxide.

[0050] The beneficial effects of the present invention are:

[0051] (1) The pulse group photo-sintering preparation method adopted in the present invention greatly broadens the photo-sintering window, is not prone to over-burning, and can effectively reduce the Pb generated during the heat treatment process. 0 state, optimizes the surface energy level state of perovskite, improves the effectiveness of photo-sintering, improves the photoelectric performance of perovskite film, and improves the steady-state fluorescence intensity of the film.

[0052] (2) In addition, the pulse group photo-sintering method has a short sintering time and exhibits good compatibility with flexible substrates and ambient atmospheres. The efficiency of the solar cell device with the prepared perovskite photoactive layer is further improved to more than 23%, and the efficiency of the prepared micro-module is more than 18%. It can be used to match industrial production while preparing perovskite solar cell devices in high throughput. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 It is the current density-voltage curve (JV curve) of perovskite solar cell devices prepared by different photo-sintering preparation methods and different sintering times. Figure 1 (a) is the JV curve of the perovskite solar cell device prepared with a sintering time of 1500 μs. Figure 1 (b) is the JV curve of the perovskite solar cell device prepared with a sintering time of 2000 μs. Figure 1 (c) is the JV curve of the perovskite solar cell device prepared with a sintering time of 2500 μs;

[0054] Figure 2 It is the statistics of the photoelectric conversion efficiency of perovskite solar cell devices with different sintering methods, different sintering times and different sintering times. Figure 2 (a) is the photoelectric conversion efficiency statistics of the perovskite solar cell device prepared with a sintering time of 1500μs. Figure 2 (b) is the photoelectric conversion efficiency statistics of the perovskite solar cell device prepared with a sintering time of 2000μs. Figure 2(c) is the statistics of the photoelectric conversion efficiency of the perovskite solar cell device prepared with a sintering time of 2500 μs;

[0055] Figure 3 The photoelectric performance results of perovskite solar cell devices prepared by three preparation methods: thermal annealing (TA), single pulse (SP) and pulse group (PG). Figure 3 The left side is the photoelectric conversion efficiency diagram. Figure 3 The right side is the current density-voltage curve (JV curve);

[0056] Figure 4 The scanning electron microscope (SEM) of the perovskite active layer films prepared by thermal annealing (TA), single pulse (SP) and pulse group (PG) preparation methods, where Figure 4 (a) is the SEM of TA, Figure 4 (b) is the SEM of SP. Figure 4 (c) in the figure is the SEM of PG;

[0057] Figure 5 The KPFM results of the perovskite active layer films prepared by thermal annealing (TA), single pulse (SP) and pulse group (PG) preparation methods are shown in Figure 2. Figure 5 (a) is the KPFM scan of TA. Figure 5 (b) is the KPFM scan of SP. Figure 5 (c) is the KPFM scan of PG. Figure 5 (d) is the contact potential difference distribution diagram of the perovskite active layer film;

[0058] Figure 6 It is the X-ray diffraction spectra (XRD) of the perovskite active layer films prepared by thermal annealing (TA), single pulse (SP) and pulse group (PG) preparation methods;

[0059] Figure 7 It is the photoluminescence spectra (PL) of perovskite active layer films prepared by thermal annealing (TA), single pulse (SP) and pulse group (PG) preparation methods;

[0060] Figure 8 GIXRD and stress analysis of perovskite active layer films prepared by thermal annealing (TA), single pulse (SP) and pulse group (PG) preparation methods

[0061] Fig. 9 It is the X-ray photoelectron spectroscopy (XPS) of Pb 4f of perovskite active layer films prepared by thermal annealing (TA) and pulse group (PG) preparation methods;

[0062] Fig.10The photoelectric performance results of the pulse group sintering device obtained by regulating the intermediate state with different additives are shown in Figure 2. Fig.10 The left side is the photoelectric conversion efficiency diagram. Fig.10 The right side is the current density-voltage curve (JV curve);

[0063] Fig.11 This is the current density-voltage curve (JV curve) of the pulse group sintering device obtained by using dimethyl sulfoxide (DMSO) as an additive to regulate the intermediate state;

[0064] Fig.12 It is the current density-voltage curve (JV curve) of the perovskite solar cell device prepared on a flexible substrate based on the pulse group sintering preparation method;

[0065] Fig.13 It is the current density-voltage curve (JV curve) of the perovskite solar cell device prepared in air atmosphere based on the pulse group sintering preparation method;

[0066] Fig.14 It is a perovskite micro-component prepared based on pulse group sintering;

[0067] Fig.15 It is FA prepared by pulse group sintering 0.9 Cs 0.1 PbI3 component perovskite solar cell devices;

[0068] Fig.16 It is FA prepared by pulse group sintering 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 ) 3-component perovskite solar cell device;

[0069] Fig.17 It is a graph showing the change in efficiency distribution of perovskite solar cell devices and sintering times under different voltages of the pulse group;

[0070] Fig.18 This is a graph showing the change in efficiency of perovskite solar cell devices with sintering times under different small pulse intervals;

[0071] Fig.19 The influence of sintering height, large pulse time interval and pulse width on device efficiency distribution;

[0072] Fig. 20 It is the influence of different hole transport layers on the efficiency distribution of devices prepared by pulse group sintering. DETAILED DESCRIPTION

[0073] The specific implementation of the present invention is further described in detail below with reference to the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are any processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art.

[0074] Example 1

[0075] The device preparation process of pulse group treatment. The perovskite solar cell device includes substrate, FTO surface electrode, hole transport layer, perovskite photoactive layer, electron transport layer, interface regulation layer and metal back electrode from bottom to top.

[0076] The perovskite solar cell device is prepared by pulse group processing, and the specific steps are as follows:

[0077] (1) Glass is selected as the substrate and FTO is selected as the conductive film to form an FTO conductive layer. Before use, the FTO conductive layer needs to be ultrasonically treated with deionized water, acetone and isopropanol in sequence, and blown dry with a high-pressure inert gas flow, and then irradiated and cleaned by ultraviolet light to remove residual organic matter and complete the surface modification.

[0078] (2) Preparation of hole transport layer: 0.3 mg of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) hole transport layer material was dissolved in 1 ml of ethanol. Then, it was dropped onto the substrate, and a layer of ultra-thin hole transport material was spin-coated on the FTO conductive layer by a coating machine, and then annealed at a certain temperature.

[0079] (3) Preparation and drying of perovskite photoactive layer: The prepared perovskite precursor solution is dripped onto the annealed hole transport layer. During the spin coating process, the spin-coated surface is dried with a certain inert gas to make the precursor solution form an intermediate state on the surface of the hole transport layer. The perovskite component is FA 0.85 MA 0.1 Cs 0.05 PbI3.

[0080] (4) Pulse group IPL sintering: The intermediate state of the perovskite precursor is transferred to the intense pulse light sintering area, and the pulse group sintering mode is selected. Under the condition of a sintering voltage of 1000 V, a pulse width of 500 μs, each pulse group contains 5 small pulses, the interval between each small pulse is 1000 μs, and the pulse interval is 1000 ms. Continuous sintering is performed at a sintering height of 40 mm. After sintering, the perovskite precursor film is completely converted into a photoactive perovskite film to obtain a perovskite photoactive layer.

[0081] (5) Preparation of electron transport layer, interface regulation layer and back electrode: The perovskite photoactive layer prepared in step (4) above is placed in a vacuum evaporation coating device, and the electron transport layer, interface regulation layer and metal back electrode are deposited in sequence. Perovskite solar cell devices with different active areas can be obtained by using different masks.

[0082] Example 2

[0083] By in component is FA 0.85 MA 0.1 Cs 0.05 0.1-4% (molar percentage) of dodecyl methyl sulfoxide is introduced into the precursor solution of PbI3 to regulate the intermediate state and obtain the perovskite photoactive layer. The specific steps are as follows:

[0084] The perovskite solar cell device includes a glass substrate, an FTO surface electrode, a hole transport layer, a perovskite photoactive layer, an electron transport layer, an interface regulation layer and a metal back electrode from bottom to top.

[0085] The perovskite solar cell device is prepared by pulse group processing, and the specific steps are as follows:

[0086] (1) Glass is selected as the substrate and FTO is selected as the conductive film to form an FTO conductive layer. Before use, the FTO conductive layer needs to be ultrasonically treated with deionized water, acetone and isopropanol in sequence, and blown dry with a high-pressure inert gas flow, and then irradiated and cleaned by ultraviolet light to remove residual organic matter and complete the surface modification.

[0087] (2) Preparation of hole transport layer: 0.3 mg of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) hole transport layer material was dissolved in 1 ml of ethanol. Then, it was dropped onto the substrate, and a layer of ultra-thin hole transport material was spin-coated on the FTO conductive layer by a coating machine, and then annealed at a certain temperature.

[0088] (3) Preparation and drying of perovskite photoactive layer: In the case of FA 0.85 MA 0.1 Cs v.05 Dodecyl MSO is introduced into the precursor solution of PbI3 to control the intermediate state, wherein the molar percentage of dodecyl MSO in the precursor solution is 0.1-4%. The prepared perovskite precursor solution is then dripped onto the annealed hole transport layer. During the spin coating process, the spin coating surface is dried with a certain inert gas to form an intermediate state on the surface of the hole transport layer.

[0089] (4) Pulse group IPL sintering: The intermediate state of the perovskite precursor is transferred to the intense pulse light sintering area, and the pulse group sintering mode is selected. Under the condition of a sintering voltage of 1000 V, a pulse width of 500 μs, each pulse group contains 5 small pulses, the interval between each small pulse is 1000 μs, and the pulse interval is 1000 ms. Continuous sintering is performed at a sintering height of 40 mm. After sintering, the perovskite precursor film is completely converted into a photoactive perovskite film to obtain a perovskite photoactive layer.

[0090] (5) Preparation of electron transport layer, interface regulation layer and back electrode: The perovskite photoactive layer prepared in step (4) above is placed in a vacuum evaporation coating device, and the electron transport layer, interface regulation layer and metal back electrode are deposited in sequence. Perovskite solar cell devices with different active areas can be obtained by using different masks.

[0091] Example 3

[0092] The preparation process of the device is the same as that of Example 2, except that the component is FA 0.85 MA 0.1 Cs 0.05 Dimethyl sulfone (MSM) is introduced into the precursor solution of PbI3 to regulate the intermediate state, wherein the molar percentage of dimethyl sulfone in the precursor solution is 0.1-4%, thereby obtaining a perovskite photoactive layer.

[0093] Example 4

[0094] The device preparation process is the same as in Example 2, except that the component is FA 0.85 MA 0.1 Cs 0.05 Dimethyl sulfoxide (DMSO) is introduced into the precursor solution of PbI3 to regulate the intermediate state, wherein the molar percentage of dimethyl sulfoxide in the precursor solution is 10-40%, thereby obtaining a perovskite photoactive layer.

[0095] Example 5

[0096] The device preparation process is the same as that of Example 1, except that a flexible substrate polyethylene naphthalate (PEN) is used to replace the original rigid glass substrate, and the voltage is adjusted to 800V.

[0097] Example 6

[0098] The device preparation process is the same as that of Example 1, except that the pulse group sintering process is carried out in an ambient atmosphere (relative humidity ~40%).

[0099] Example 7

[0100] The perovskite micromodule includes a glass substrate, an FTO surface electrode, a hole transport layer, a perovskite photoactive layer, an electron transport layer, an interface regulation layer, and a metal back electrode from bottom to top. Each sub-cell is monolithically interconnected through laser scribing systems P1, P2, and P3. The specific steps are as follows:

[0101] (1) The FTO conductive layer substrate is divided into sub-cells through P1 processing of the laser scribing system.

[0102] (2) The FTO conductive layer substrate of each sub-cell must first be ultrasonically treated with deionized water, acetone and isopropanol in sequence, and blown dry with a high-pressure inert gas flow, and then cleaned by ultraviolet light to remove residual organic matter and complete the surface modification.

[0103] (2) Preparation of hole transport layer: 0.3 mg of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) hole transport layer material was dissolved in 1 ml of ethanol. Then, it was dropped onto the substrate, and a layer of ultra-thin hole transport material was spin-coated on the FTO conductive layer by a coating machine, and then annealed at a certain temperature.

[0104] (3) Preparation and drying of perovskite photoactive layer: The prepared perovskite precursor solution is dripped onto the annealed hole transport layer. During the spin coating process, the spin-coated surface is quickly dried with a nitrogen gas flow, so that the precursor solution forms an intermediate state on the surface of the hole transport layer. The perovskite component is FA 0.85 MA 0.1 Cs 0.05 PbI3.

[0105] (4) Pulse group IPL sintering: The intermediate state of the perovskite precursor is transferred to the intense pulse light sintering area, and the pulse group sintering mode is selected. Under the condition of a sintering voltage of 1000 V, a pulse width of 500 μs, each pulse group contains 5 small pulses, the interval between each small pulse is 1000 μs, and the pulse interval is 1000 ms. Continuous sintering is performed at a sintering height of 40 mm. After sintering, the perovskite precursor film is completely converted into a photoactive perovskite film to obtain a perovskite photoactive layer.

[0106] (5) Preparation of electron transport layer, interface regulation layer and back electrode: Place the perovskite photoactive layer prepared in step (4) above into a vacuum evaporation coating device, deposit the electron transport layer and the interface regulation layer in sequence, and then place it into a laser scribing system for P2 scribing;

[0107] After P2 scribing, the metal back electrode is vacuum evaporated, and then P3 scribing is completed again by a laser scribing system to form an effective series connection of each sub-battery.

[0108] Example 8

[0109] The device preparation process is the same as in Example 1, except that the perovskite component is FA 0.9 Cs 0.10 PbI3.

[0110] Example 9

[0111] The device preparation process is the same as in Example 1, except that the perovskite component is FA 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3.

[0112] Example 10

[0113] The device preparation process is the same as that of Example 1, except that the sintering voltage is changed from 1000V to 900V.

[0114] Embodiment 11

[0115] The device preparation process is the same as that of Example 1, except that the sintering voltage is changed from 1000V to 1100V.

[0116] Example 12

[0117] The device preparation process is the same as that of Example 1, except that the pulse width is changed from 500 μs to 450 μs.

[0118] Example 13

[0119] The device preparation process of the pulse group treatment is the same as that of Example 1, except that each pulse group contains 3 small pulses.

[0120] Embodiment 14

[0121] The device preparation process of the pulse group treatment is the same as that of Example 1, except that each pulse group contains 4 small pulses.

[0122] Embodiment 15

[0123] The device preparation process for pulse group treatment is the same as that in Example 1, except that the interval between each small pulse is changed from 1000 μs to 2000 μs.

[0124] Example 16

[0125] The device preparation process for pulse group treatment is the same as that in Example 1, except that the interval between each small pulse is changed from 1000 μs to 3000 μs.

[0126] Embodiment 17

[0127] The device preparation process for pulse group treatment is the same as that in Example 1, except that the pulse maximum interval is changed from 1000 ms to 750 ms.

[0128] Embodiment 18

[0129] The device preparation process of the pulse group treatment is the same as that of Example 1, except that the sintering height is changed from 40 mm to 38 mm.

[0130] Embodiment 19

[0131] The device preparation process for the pulse group treatment is the same as that in Example 1, except that the hole transport material is a 0.9 mg / ml ethanol solution of 4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz).

[0132] Comparative Example 1

[0133] The device preparation process of traditional thermal annealing treatment. The perovskite solar cell device includes substrate, FTO surface electrode, hole transport layer, perovskite photoactive layer, electron transport layer, interface regulation layer and metal back electrode from bottom to top.

[0134] The perovskite solar cell device is prepared by conventional thermal annealing treatment, and the specific steps are as follows:

[0135] (1) Glass is selected as the substrate and FTO is selected as the conductive film to form an FTO conductive layer. Before use, the FTO conductive layer needs to be ultrasonically treated with deionized water, acetone and isopropanol in sequence, and blown dry with a high-pressure inert gas flow, and then irradiated and cleaned by ultraviolet light to remove residual organic matter and complete the surface modification.

[0136] (2) Preparation of hole transport layer: 0.3 mg of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) hole transport layer material was dissolved in 1 ml of ethanol. Then, it was dropped onto the substrate, and a layer of ultra-thin hole transport material was spin-coated on the FTO conductive layer by a coating machine, and then annealed at a certain temperature.

[0137] (3) Preparation and drying of perovskite photoactive layer: The prepared perovskite precursor solution is dripped onto the annealed hole transport layer. During the spin coating process, the spin-coated surface is dried with a certain inert gas to make the precursor solution form an intermediate state on the surface of the hole transport layer. The perovskite component is FA 0.85 MA 0.1 Cs 0.05 PbI3.

[0138] (4) Thermal annealing: The intermediate perovskite precursor film in step (3) is transferred to a hot plate for annealing for 30 minutes to completely transform the perovskite precursor film into a photoactive perovskite film, thereby obtaining a perovskite photoactive layer.

[0139] (5) Preparation of electron transport layer, interface regulation layer and back electrode: The perovskite photoactive layer prepared in step (4) above is placed in a vacuum evaporation coating device, and the electron transport layer, interface regulation layer and metal back electrode are deposited in sequence. Perovskite solar cell devices with different active areas can be obtained by using different masks.

[0140] Comparative Example 2

[0141] The device preparation process of single pulse processing. The perovskite solar cell device includes substrate, FTO surface electrode, hole transport layer, perovskite photoactive layer, electron transport layer, interface regulation layer and metal back electrode from bottom to top.

[0142] The perovskite solar cell device is prepared by single pulse processing, and the specific steps are as follows:

[0143] (1) Glass is selected as the substrate and FTO is selected as the conductive film to form an FTO conductive layer. Before use, the FTO conductive layer needs to be ultrasonically treated with deionized water, acetone and isopropanol in sequence, and blown dry with a high-pressure inert gas flow, and then irradiated and cleaned by ultraviolet light to remove residual organic matter and complete the surface modification.

[0144] (2) Preparation of hole transport layer: 0.3 mg of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) hole transport layer material was dissolved in 1 ml of ethanol. Then, it was dropped onto the substrate, and a layer of ultra-thin hole transport material was spin-coated on the FTO conductive layer by a coating machine, and then annealed at a certain temperature.

[0145] (3) Preparation and drying of perovskite photoactive layer: The prepared perovskite precursor solution is dripped onto the annealed hole transport layer. During the spin coating process, the spin-coated surface is dried with a certain inert gas to make the precursor solution form an intermediate state on the surface of the hole transport layer. The perovskite component is FA 0.85 MA 0.1 Cs 0.05 PbI3.

[0146] (4) Single-pulse IPL sintering: The intermediate state of perovskite is transferred to the intense pulse light sintering area, and the single-pulse sintering mode is selected. Under the condition of a sintering voltage of 1000 V, continuous sintering is performed with a pulse width of 1500 μs, a large pulse interval of 1000 ms, and a sintering height of 40 mm. After sintering, the perovskite precursor film is completely converted into a photoactive perovskite film to obtain a perovskite photoactive layer.

[0147] (5) Preparation of electron transport layer, interface regulation layer and back electrode: The perovskite photoactive layer prepared in step (4) above is placed in a vacuum evaporation coating device, and the electron transport layer, interface regulation layer and metal back electrode are deposited in sequence. Perovskite solar cell devices with different active areas can be obtained by using different masks.

[0148] Comparative Example 3

[0149] The device preparation process is the same as that of Comparative Example 2, except that the pulse width of the single-pulse sintering mode is 2000 μs.

[0150] Comparative Example 4

[0151] The device preparation process is the same as that of Comparative Example 2, except that the pulse width of the single-pulse sintering mode is 2500 μs.

[0152] Test Example 1

[0153] The photoelectric properties of the perovskite solar cell devices prepared in Examples 1, 13, 14 and Comparative Examples 2, 3, 4 were analyzed.

[0154] Under the conditions of simulated AM 1.5 sunlight (light intensity of 100mW / cm 2 ) tested the perovskite solar cell devices prepared by different photo-sintering methods and different sintering times. For the pulse group, the sintering time was controlled by the sintering parameters of the pulse group, and the sintering time of a single pulse was determined by the pulse width; the reverse scanning voltage range was 1.2V~-0.2V, the forward scanning voltage range was -0.2V~1.2V, the scanning rate was 20mV / s, and the active area of ​​the device was 0.04cm 2 Table 1 Photoelectric performance parameters of perovskite solar cell devices prepared by different photo-sintering methods and different sintering times

[0155]

[0156] From Table 1 and Figure 1 The results show that the filling factor (FF) of the perovskite solar cell device sintered by pulse group has been greatly improved. In addition, the hysteresis effect of the pulse group sintering is lower than that of the perovskite solar cell device sintered by single pulse, and the device sintered by pulse group is higher than that of the device made by single pulse sintering, which proves that pulse group sintering plays a role in improving the photoelectric performance of perovskite solar cell devices.

[0157] Test Example 2

[0158] The effects of different sintering times in Examples 1, 13, 14 and Comparative Examples 2, 3, 4 were analyzed. Figure 2It is the statistics of the photoelectric conversion efficiency of perovskite solar cell devices with different sintering methods, different sintering times and different sintering times. Figure 2 (a) is the photoelectric conversion efficiency statistics of the perovskite solar cell device prepared with a sintering time of 1500μs. Figure 2 (b) is the photoelectric conversion efficiency statistics of the perovskite solar cell device prepared with a sintering time of 2000μs. Figure 2 (c) is the photoelectric conversion efficiency statistics of the perovskite solar cell device prepared with a sintering time of 2500 μs. Under each condition, an active area of ​​0.04 cm 2 The photoelectric conversion efficiency of 8 batteries was analyzed.

[0159] Depend on Figure 2 The results show that the perovskite solar cell device prepared by pulse group sintering has higher photoelectric conversion efficiency and a wider sintering window range than the perovskite solar cell device prepared by single pulse sintering. This can greatly reduce the probability of device burning and improve the product yield in actual industrial production.

[0160] Test Example 3

[0161] The photoelectric properties of the perovskite solar cell devices prepared by the three preparation methods in Example 1 and Comparative Examples 1 and 4 were analyzed. Figure 3 The photoelectric performance results of perovskite solar cell devices prepared by three preparation methods: thermal annealing (TA), single pulse (SP) and pulse group (PG). Figure 3 The left side is the photoelectric conversion efficiency diagram. Figure 3 The right side is the current density-voltage curve (JV curve).

[0162] Test sample selection: single pulse sintering, single sintering time is 2500μs, sintering times are 4 times; single pulse group sintering, single sintering time is 2500μs, sintering times are 9 times.

[0163] Depend on Figure 3 The results show that the photoelectric conversion efficiency of the device prepared by the single-pulse preparation method is slightly lower than that of thermal annealing, while the photoelectric conversion efficiency of the device processed by the pulse group is significantly improved compared with the single pulse, and is also slightly improved compared with thermal annealing; in addition, the device processed by the pulse group has the highest current density and fill factor, and its comprehensive performance is better than that of the devices prepared by thermal annealing and single pulse.

[0164] Test Example 4

[0165] The microscopic morphology of the perovskite photoactive layer films prepared by the three preparation methods in the embodiments and comparative examples was characterized by a scanning electron microscope (SEM). Figure 4The scanning electron microscope (SEM) of the perovskite active layer films prepared by thermal annealing (TA), single pulse (SP) and pulse group (PG) preparation methods, where Figure 4 (a) is the SEM of TA, Figure 4 (b) is the SEM of SP. Figure 4 (c) in the figure is the SEM of PG.

[0166] Test sample selection: single pulse sintering, single sintering time is 2500μμs, sintering times are 4 times; single pulse group sintering, single sintering time is 2500μs, sintering times are 9 times.

[0167] Depend on Figure 4 The results show that compared with the devices prepared by thermal annealing, the grains of the perovskite photoactive layer films prepared by single pulse and pulse group preparation methods are relatively large, which can reduce the influence of grain boundaries on carrier transport.

[0168] Test Example 5

[0169] The contact potential difference (CPD) of the perovskite photoactive layer films prepared by the three preparation methods in the examples and comparative examples was analyzed using a Kelvin probe microscope (KPFM), as follows:

[0170] KPFM is used to further evaluate the surface potential of the perovskite photoactive layer, which is related to the work function. The work function of the perovskite photoactive layer is determined by the contact potential difference (CPD) between the conductive probe tip and the sample surface, and the calculation formula is CPD = (Φ tip -Φ sample ) / e, where Φ tip is the work function of the needle tip, Φ sample is the work function of the sample, e is the electron charge). tip is a constant, so the work function of the sample is inversely proportional to the CPD.

[0171] Figure 5 The KPFM results of the perovskite active layer films prepared by thermal annealing (TA), single pulse (SP) and pulse group (PG) preparation methods are shown in Figure 1. Figure 5 (a) is the KPFM scan of TA. Figure 5 (b) is the KPFM scan of SP. Figure 5 (c) is the KPFM scan of PG. Figure 5 (d) in the figure is the contact potential difference distribution diagram of the perovskite active layer film.

[0172] Test sample selection: single pulse sintering, single sintering time is 2500μμs, sintering times are 4 times; single pulse group sintering, single sintering time is 2500μs, sintering times are 9 times; the sampling area of ​​the three preparation methods is 4cm2 .

[0173] Depend on Figure 5 The results show that the perovskite film made by hot plate annealing has a lower CPD≈-325±25mV, the perovskite photoactive layer film prepared by single pulse sintering has a higher CPD≈-175±25mV, and the perovskite photoactive layer film prepared by pulse group sintering has a CPD≈-210±25mV. The higher the CPD, the smaller the work function of the film, and it is easier to show strong n-type characteristics, so that the electron transport layer can form a stronger interface electric field with it, which is convenient for the extraction of carriers (here, electrons). Therefore, the perovskite photoactive layer film prepared by pulse group sintering is more conducive to the transmission of carriers than thermal annealing.

[0174] Test Example 6

[0175] The perovskite photoactive layer films prepared by the three preparation methods in the examples and comparative examples were analyzed using an X-ray diffractometer (XRD). Figure 6 Shown are the XRD patterns of different preparation methods.

[0176] Test sample selection: single pulse sintering, single sintering time is 2500μs, sintering times are 4 times; single pulse group sintering, single sintering time is 2500μs, sintering times are 9 times.

[0177] Depend on Figure 6 The results show that in traditional thermal annealing, due to the continuous thermal action, the additional PbI2 peak is more obvious. For the perovskite photoactive layer film prepared by either single pulse (SP) or pulse group (PG), no additional PbI2 peak appears, indicating that the pulse sintering method can effectively reduce the PbI2 generated during the heat treatment process. 0 state, optimizing the effectiveness of photosintering.

[0178] Test Example 7

[0179] The photoluminescence spectra (PL) of the perovskite photoactive layer films prepared by the three preparation methods in Example 1 and Comparative Examples 1 and 4 were analyzed to characterize the defect density, such as Figure 7 Shown are the PL spectra of different preparation methods.

[0180] Test sample selection: single pulse sintering, single sintering time is 2500μs, sintering times are 4 times; single pulse group sintering, single sintering time is 2500μs, sintering times are 9 times; the sample area of ​​the three preparation methods is 4cm 2 .

[0181] Depend on Figure 7From the results, it can be seen that compared with the perovskite photoactive layer film treated with thermal annealing (TA), the PL peaks of single pulse (SP) and pulse group (PG) are blue-shifted, but the PL intensities of single pulse (SP) and pulse group (PG) treatments are improved compared with TA, especially the PL intensity of pulse group (PG) treatment is the highest among the three, indicating that the defect density of the perovskite photoactive layer film treated with PG is greatly reduced.

[0182] Test Example 8

[0183] The residual stress of the perovskite photoactive layer films prepared by the three preparation methods in Example 1 and the comparative example was analyzed. Figure 8 Shown are the GIXRD spectra of perovskite active layer films prepared by thermal annealing (TA), single pulse (SP) and pulse group (PG) preparation methods at different tilt angles.

[0184] Test sample selection: In single pulse sintering, the single sintering time is 2500μs, and the number of sintering times is 34 times; in pulse group sintering, the single sintering time is 2500μs, and the number of sintering times is 9 times.

[0185] Depend on Figure 8 The results show that with the increase of the tilt angle (ψ), the diffraction peak of the thermally annealed (TA) sample shifts to a lower angle, indicating the presence of a more obvious residual tensile stress. The shift of the single pulse (SP) is much smaller, while the shift of the pulse group (PG) has a very obvious change, from 2θ-sin 2 It can be seen from ψ that the residual stress of PG is reduced by more than one order of magnitude than that of TA.

[0186] Test Example 9

[0187] The Pb element of the perovskite photoactive layer film prepared by the preparation methods of Example 1 and Comparative Example 1 was analyzed. Fig. 9 Shown are the XPS spectra of Pb 4f in perovskite active layer films prepared by thermal annealing (TA) and pulse group (PG) preparation methods.

[0188] Test sample selection: The single sintering time in the pulse group sintering is 2500μs, and the sintering times are 9 times.

[0189] Depend on Fig. 9 The results show that the Pb of the perovskite photoactive layer film treated by the pulse group (PG) 2+ The peak slightly shifts to lower binding energy. The most critical point is that Pb appears in the photoactive layer of the perovskite film treated with TA. 0 peak, while PG treatment makes Pb 0 The peak almost completely disappeared, proving that the pulse group sintering preparation method has a good effect on maintaining the chemical composition of the perovskite surface.

[0190] Test Example 10

[0191] In order to illustrate the effect of different additives on the efficiency of perovskite solar cell devices, Examples 1 to 4 were analyzed. Fig.10 and Fig.11 The photoelectric performance results of the pulse group sintering device obtained by regulating the intermediate state with different additives are shown in the figure. Fig.10 The left side is the photoelectric conversion efficiency diagram. Fig.10 The right side of is the current density-voltage curve (JV curve), where the additives are dimethyl sulfone (MSM) and dodecyl methyl sulfoxide (DodecylMSO), wherein the Control group is the device prepared in Example 1 (standard group), Fig.11 The additive is dimethyl sulfoxide (DMSO) and under the conditions of pulse group photosintering, it can also achieve a photoelectric conversion efficiency of more than 22%, exceeding that of the standard group.

[0192] Depend on Fig.10 and Fig.11 The results show that the introduction of strongly coordinated components such as dodecyl methyl sulfoxide or dimethyl sulfoxide can greatly increase the open circuit voltage, and the fill factor and current density of the device are also improved. The photoelectric conversion efficiency of dodecyl methyl sulfoxide (DodecylMSO) exceeds 23%, and the photoelectric conversion efficiency of dimethyl sulfoxide (DMSO) also exceeds 22%, both exceeding the standard group.

[0193] Test Example 11

[0194] In addition, since the heat generated by photo-sintering is transient, it has great advantages for substrates that are sensitive to temperature. The performance of the device prepared in Example 5 is analyzed. Fig.12 Shown is the current density-voltage curve (JV curve) of a perovskite solar cell device prepared on a flexible PEN substrate based on a pulse group sintering preparation method.

[0195] Depend on Fig.12 The results show that the photoelectric conversion efficiency of the device prepared by the pulse group sintering method reaches more than 20%, indicating that pulse group sintering has good application potential on flexible and heat-sensitive substrates.

[0196] Test Example 12

[0197] In order to effectively match the industrial production of solar cells, the performance of the solar cells prepared under the environmental atmosphere of Example 6 was characterized. Fig.13 The current density-voltage curve (JV curve) of the perovskite solar cell device prepared based on the pulse group sintering preparation method in an ambient atmosphere (relative humidity ~40%) is given.

[0198] Depend on Fig.13The results show that the photoelectric conversion efficiency of perovskite solar cell devices prepared in ambient atmosphere (relative humidity - 40%) also exceeded 20%, indicating that rapid pulse group sintering can greatly improve the tolerance to humidity and oxygen in the air atmosphere, providing a feasible solution for the future processing of perovskite devices in air.

[0199] Test Example 13

[0200] The performance of the perovskite solar micromodule prepared in Example 7 was characterized. Fig.14 A pulse group sintering preparation method is given at 25cm 2 Current density-voltage curve (JV curve) of perovskite solar micromodule prepared on a substrate.

[0201] Depend on Fig.14 The results show that the pulse group sintering has good scalability. 2 A photoelectric conversion efficiency of more than 18% was achieved on the micro-components, expanding the application scenarios of pulse group sintering.

[0202] Test Example 14

[0203] To verify the universality of pulse group sintering, the optical properties of the remaining perovskite components were characterized. Fig.15 and Fig.16 The composition prepared by pulse group sintering is FA 0.9 Cs 0.10 PbI3 and FA 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 of the perovskite solar cell device with current density-voltage curve (JV curve).

[0204] Fig.15 and Fig.16 The results show that from FA and Cs binary A-site perovskite to Br-containing perovskite, the composition is FA 0.9 Cs 0.10 PbI3 and FA 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3's perovskite solar cell device efficiency has reached about 20%, reflecting the relative universality of pulse group photosintering for perovskite components.

[0205] Test Example 15

[0206] A series of corresponding comparisons were conducted on the effects of various pulse group parameters on device performance:

[0207] Solar cell devices prepared based on different pulse group voltages (Examples 1, 10 and 11), such as Fig.17 As shown, different voltages correspond to different xenon lamp energies, which will affect the sintering times for the perovskite device to reach the local optimal value, but the local optimal values ​​are relatively close;

[0208] The change of pulse width in Example 12 can change the corresponding energy and achieve device efficiency similar to that of Example 1 within a reasonable range;

[0209] The interval of the small pulses in Examples 15 and 16 can control the waiting time value of the perovskite active layer at the target temperature, such as Fig.18 As shown, it has little effect on the local optimal value of the device, but has a certain impact on the distribution of the device;

[0210] The pulse interval of Example 17 and the sintering height of Example 18 are within a reasonable range, which has little effect on the sintering strength and temperature change. Fig.19 shown.

[0211] Test case 16

[0212] The effects of different hole transport layers on the devices prepared by pulse group sintering were compared between Example 1 and Example 19. Fig. 20 As shown, in the same batch of devices, two different self-assembled phosphonic acids (MeO-2PACz and MeO-4PACz) gave similar highest champion points, and the distribution of MeO-4PACz devices was slightly better, but overall it shows that pulse group sintering can be applied to different hole transport layers.

Claims

1. A method for preparing a perovskite photoactive layer by photo-sintering, characterized in that: The following steps are involved: (1) preparing a precursor solution of a perovskite photoactive layer; (2) spreading the precursor solution of the perovskite photoactive layer prepared in step (1) on the hole transport layer substrate, and extracting it to form a perovskite intermediate state; (3) Using an intense pulsed light sintering method, the perovskite intermediate state obtained in step (2) is subjected to pulsed light sintering to obtain a perovskite photoactive layer.

2. The method for preparing the perovskite photoactive layer by photo-sintering according to claim 1, characterized in that: The precursor solution of the perovskite photoactive layer contains crystals of ABX3 perovskite structure; wherein A is one or more of methylammonium cation, formamidinium cation, cesium ion, and rubidium ion, B is one or more of lead ion and tin ion, and X is one or more of chloride ion, bromide ion, iodide ion, and thiocyanate ion.

3. The method for preparing the perovskite photoactive layer by photo-sintering according to claim 1, characterized in that: Sulfone or sulfoxide additives are added to the precursor solution of the perovskite photoactive layer.

4. The method for preparing the perovskite photoactive layer by photo-sintering according to claim 3, characterized in that: The sulfone or sulfoxide additive added to the precursor solution is dimethyl sulfone, dodecyl methyl sulfoxide or dimethyl sulfoxide.

5. The method for preparing the perovskite photoactive layer by photo-sintering according to claim 3 or 4, characterized in that: The molar percentage of the sulfone or sulfoxide additive in the precursor solution of the perovskite photoactive layer is 0.1-40%.

6. The method for preparing the perovskite photoactive layer by photo-sintering according to claim 1, characterized in that: The precursor solution is spread by spin coating, blade coating or slit coating.

7. The method for preparing the perovskite photoactive layer by photo-sintering according to claim 1, characterized in that: The extraction is carried out by air knife, anti-solvent or vacuum drying.

8. The method for preparing the perovskite photoactive layer by photo-sintering according to claim 1, characterized in that: The pulse group light sintering is to place the perovskite intermediate state into the light sintering cavity, and adjust the pulse group light sintering parameters to implement the pulse group light sintering process.

9. The method for preparing the perovskite photoactive layer by photo-sintering according to claim 8, characterized in that: The pulse group optical sintering parameters are: sintering voltage 500-2000V, pulse width 1-3000μs, each pulse group contains 1-15 small pulses, the interval between each small pulse is 5-3000μs, and the pulse maximum interval is 5N10000ms.

10. The method for preparing the perovskite photoactive layer by photo-sintering according to claim 9, characterized in that: The pulse group light sintering process is as follows: the sintering height between the pulse light source and the photoactive layer is ≤1000mm, and the number of sintering times is ≤50 times.

11. A perovskite photoactive layer prepared by the photo-sintering preparation method of a perovskite photoactive layer according to any one of claims 1 to 10.

12. The perovskite photoactive layer according to claim 11, characterized in that: The perovskite photoactive layer is FA 1-x-y MA x Cs y Pb(I 1-z Br z )3, where x=0~1, y=0~1, z=0-1.

13. A solar cell device or micromodule comprising the ABX3 perovskite photoactive layer according to claim 11 or 12.

14. The solar cell device or micromodule according to claim 13 comprises a substrate, a surface electrode, a hole transport layer, an ABX3 perovskite photoactive layer, an electron transport layer, an interface regulation layer and a back electrode, characterized in that: The substrate is a flexible substrate or glass; the hole transport layer is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], copper thiocyanate, aluminum oxide, nickel oxide and / or single-molecule self-assembled phosphonic acid.

15. The solar cell device or micromodule according to claim 13, characterized in that: The flexible substrate is polyethylene terephthalate, polyethylene naphthalate, polyimide or ultra-thin flexible glass.

16. The solar cell device or micromodule according to claim 13, characterized in that: The single-molecule self-assembling phosphonic acid is [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(7H-dibenzo[c,g]carbazole-7-yl)butyl]phosphonic acid, [4-(3,11-dimethoxy-7H-dibenzo[c,g]carbazole-7-yl)butyl]phosphonic acid, [2,7-dimethoxy-9-hydrogen-carbon-azole-9-yl)methyl]phosphonic acid, [2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid or [2-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid.

17. The solar cell device or micromodule according to claim 13, characterized in that: Solar cell devices or micro-modules include: FA 0.85 MA 0.1 Cs 0.05 PbI3 perovskite photoactive layer; in the preparation of FA 0.85 MA 0.1 Cs 0.05 When the PbI3 perovskite photoactive layer is prepared, a sulfone or sulfoxide additive is added to the precursor solution of the perovskite photoactive layer, and the sulfone or sulfoxide additive is dodecyl methyl sulfoxide.

Citation Information

Patent Citations

  • Annealing method and device of large-area perovskite film layer and application of annealing method and device

    CN114843409A

  • Method for optimizing NiOx / SAM hole transport layer of perovskite solar cell

    CN118555884A

  • Method for manufacturing a perovskite thin film, and method for manufacturing a fuel cell using same

    KR1020170052816A

  • Methods for forming a perovskite solar cell

    US20170250030A1

  • Rapid layer-specific photonic annealing of perovskite thin films

    US20200127204A1